Numerical conformal mapping and its inverse of unbounded multiply connected regions onto logarithmic spiral slit regions and straight slit regions - Yunus A.A.M.; Murid A.H.M.; Nasser M.M.S. (Royal Society, 2024)
Indexed by WOS/ Scopus